2020
DOI: 10.1364/oe.388153
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high resolution and broadband chip-scale speckle enhanced Fourier-transform spectrometer

Abstract: Recent advancements in silicon photonics are enabling the development of chip-scale photonics devices for sensing and signal processing applications. Here we report on a novel passive, chip-scale, hybrid speckle-enhanced discrete Fourier transform device that exhibits a two order-of-magnitude improvement in finesse (bandwidth/resolution) over the current state-of-the art chip-scale waveguide speckle and Fourier transform spectrometers reported in the literature. In our proof-of-principle device, we demonstrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Figure 8 shows an example of the entire photonic architecture for reservoir computing. The multimode waveguide with a spiral geometry or interferometer structure fabricated on a silicon chip can provide a long optical path length and high NA to generate speckles sensitive to the wavelength [34,35,36]; further, it can be used to induce speckle dynamics with a shorter latency in a small footprint. Each signal from the multimode waveguide can be split by a splitter and wavelength demultiplexer and detected by the photodetector array.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Figure 8 shows an example of the entire photonic architecture for reservoir computing. The multimode waveguide with a spiral geometry or interferometer structure fabricated on a silicon chip can provide a long optical path length and high NA to generate speckles sensitive to the wavelength [34,35,36]; further, it can be used to induce speckle dynamics with a shorter latency in a small footprint. Each signal from the multimode waveguide can be split by a splitter and wavelength demultiplexer and detected by the photodetector array.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[ 91 ] In the same year, Paudel et al proposed a speckle enhanced SHS with a spectral resolution of 140 MHz and 12 nm bandwidth for a finesse of 104 that can operate over a range of 1500–1600 nm. [ 92 ] Xia et al used an artificial neural networks to analyze the output stationary interferogram, and the resolution could be improved without increasing the maximum path length difference and the number of MZIs, thus reducing the burden of adding more power budget. [ 93 ] In 2021, Dinh et al proposed and experimentally demonstrated the Jacquinot's advantage for the first time with 13 dB étendue increase, compared with a device with a conventional grating coupler input.…”
Section: On‐chip Ftssmentioning
confidence: 99%
“…Optical spectroscopy is an indispensable tool in the studies of matter and light, including chemistry 1 , 2 , astronomy 3 , biology and medicine 4 , metrology, and more. Yet, the resolution of all state-of-the-art methods, such as grating-based 5 , 6 and Fourier spectrometers 7 9 , is subject to the Fourier limit. Methods of beating analogous Rayleigh limit are widely known in the context of imaging and include modifying or exploiting very specific properties of the source or illumination 10 – 13 , which is often impossible to implement.…”
Section: Introductionmentioning
confidence: 99%